Estudio de factibilidad para la implantación de un software para el control del personal del Comercial El Sol, de la Parroquia San Juan del cantón Pueblo Viejo - Mendoza Monserrate, Darwin Omar (2021)
This research is a feasibility study for the implementation of a software for the control of the commercial personnel that arises from the irregularities presented at the time of registering the attendance of the personnel and the difficulties that this brings when the reports of pay or pay roles. The entry and exit records are vulnerable to modification by the workers themselves since they are the ones who make their registration manually in a notebook, thus exposing themselves to recording an entry or exit time other than the real. For this reason, it is offered to use a computer system that allows control through a biometric system which was concluded that it would be a possible alternative for the director of said commercial, this system will admit the fingerprint of each individual, this kind of technology is widely used nowadays, one of the reasons why it is at its peak is that it is guaranteed that no one will be able to do the registration impersonating another person because the fingerprint is exclusive in all workers . Reducing the participation of human resources in the manipulation of this information so considerable for the company. In addition, having an exact record of the hours worked for each worker makes it possible to generate payment reports or payment permits, thus avoiding employees demanding that they be paid for hours not worked, and it will also be registered in the system when a worker has breaches in their working hours, to take it into account at the moment of creating their payment. By having a digital record of the entry and exit times, the lack of data is prevented since at present they tend to hide the sheets where all this information is recorded, assuring that the data is complete in a single system which only be handled by a security individual. With all the aforementioned, it will be possible for workers to arrive on time to their work, the time with which payment permits are issued will be shortened and the economic losses for values that were already paid before the work will be reduced.